STRATEGI GURU AKIDAH AKHLAK DALAM MENANAMKAN KARAKTER SOPAN SANTUN PESERTA DIDIK KELAS V B DI MADRASAH IBTIDAIYAH SWASTA AT-TAQWA SAMBAS - Wiwit Destu; Nuraini; Topik (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
The purpose of this study was to reveal, abaut 1) Preparation of Akidah Akhak teacher in instilling the character of courtesy of class V B student at Madrasah Ibtidaiyah At-Taqwa Sambas. 2) presentation of the strategy of Akidah Akhlak teachers in instilling the character of courtesy of class V B students at the At-Taqwa Sambas private Madrasah Ibtidaiyah. 3) the supporting and inhibiting factors of the Akidah Akhlak teachers in instilling the character of courtesy of class V B students in At-Taqwa Sambas private Ibtidaiyah Madrasah. This research uses descriptive research with a qualitative approach. Data collection techniques using interviews, observation, and documentation. The data analysis techniques used are data reduction, data display, and concolusions. The results showed that; 1) preparation of Akidah Akhlak teacher strategis in instialling the character of courtesy of class V B student at Madrasah Ibtidaiyah private At-Taqwa Sambas for the 2019-2020 school year was carried out by 7 generating student motivation and interest, a) prepare mentally, b) aurouse student motivation and interest, c) stimulating and aurousing student curiosity, d) setting up an atmosphere and open learning climate, e) positive suggestions for students, f) delivering learning objectives, g) opening students’ insights. 2) presentation of Akidah Akhlak teacher strategies in instilling the character of courtesy of class V B students at At-Taqwa Sambas private Madrasah Ibtidaiyah for the 2019-2020 academic year are carried out in 7 ways, namely: a) communicative language according to student development, b) intonasi voice in delivering material, c) eye contact with students, d) refreshing joke-jokes, e) repeating material, f) asking questions, g) mapping of material successful or not 3) supporting and inhibiting factors for Akidah Akhlak teachers in instilling the caracthers in instilling the character of courtesy class V B students at At-Taqwa Sambas private Madrasah Ibtidaiyah for the 2019-2020 academic year are carried out in 4 ways, namely: a) using adequate facilities. b) motivation from parents, c) delivery of material, d) difficulty understanding for students.